Hope, Illness and Counselling Practice: Making Hope Visible - Edey, Wendy; Jevne, Ronna F. (Canadian Journal of Counselling and Psychotherapy, 2007)
Normally hope operates as a silent factor in counselling, playing a subordinate role to discussion of the problem. However, hope can be consciously tracked and given attention as a central feature. Through the use of hope-focussed questions, and language which conveys hope, counsellors can capitalize on opportunities to make hope visible to themselves and their clients. This article draws on some of the literature from the fields of nursing and psychology which links counselling practice, hope, and illness. The authors address the issue of false hope and the challenge of being a hopeful counsellor. Two working examples are used to suggest and briefly demonstrate interventions counsellors might make if they choose to reflect on hope as they do their work.